Democratising the IMF: Involving parliamentarians - Andrew C. Eggers; Ann M. Florini; Ngaire Woods (University of Oxford, Global Economic Governance Programme (GEG), 2005)
Calls for the IMF to increase participation in decision-making present a compelling case from numerous sources. Any organization working to meet and further its clients' needs requires feedback from those affected, to maintain quality and relevance. IMF lending typically takes place during a crisis with little time for broad democratic consultations. If the Fund's role is not to be coercive, broader society participation must precede the crisis, part of the normal politics of engagement. Despite the need for greater participation and legitimacy in the IMF, little rigorous thought has been applied to how this might practically be brought about. This paper argues that the involvement of national Parliaments is an obvious beginning. It evaluates the status of parliamentary involvement to date and analyses how Parliamentarians and the IMF can improve and expand parliamentary oversight.
Keywords: 330